2013
DOI: 10.1371/journal.pone.0064741
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vacuum-Assisted Closure (VAC) Therapy on Clinical Outcomes of Patients with Sternal Wound Infections: A Meta-Analysis of Non-Randomized Studies

Abstract: ObjectiveTo examine the impact of VAC therapy on mortality of patients with sternal wound infections after cardiothoracic surgery.Summary Background DataControversial results regarding mortality of patients with sternal wound infections were published.MethodsWe performed a systematic search in PubMed and Scopus. Mortality was the primary outcome of the meta-analysis. Recurrences, complications and length of stay were secondary outcomes.ResultsTwenty-two retrospective studies including 2467 patients were eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
1
28
1
2
Order By: Relevance
“…However, complications occurred in up to 18% of patients treated with this approach [16,92] . Several recent studies, meta-analyses, and systematic reviews have validated the efficacy of NPWT in DSWI either as a single-line therapy, or as a "bridge" prior to final surgical closure [93][94][95][96][97] . This wound-healing technique is based on the application of continuous or intermittent negative pressure to a wound, which results in arteriolar dilatation and, subsequently, determines wound perfusion and granulation tissue proliferation [57,85,93] .…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…However, complications occurred in up to 18% of patients treated with this approach [16,92] . Several recent studies, meta-analyses, and systematic reviews have validated the efficacy of NPWT in DSWI either as a single-line therapy, or as a "bridge" prior to final surgical closure [93][94][95][96][97] . This wound-healing technique is based on the application of continuous or intermittent negative pressure to a wound, which results in arteriolar dilatation and, subsequently, determines wound perfusion and granulation tissue proliferation [57,85,93] .…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…In vitro and clinical studies designed to determine the effect of NPWT lent convincing evidence of efficacy and safety in term of decrease of edema, exudation, and microbial colonization as well as reduction of inflammatory cytokine release [57,85,[98][99][100] . In case of diagnosis of DSWI, an early application of NPWT was associated to a faster healing and an increased likelihood of survival [18,97,101,102] . Moreover, several studies demonstrated shorter treatment duration and length of hospital stay, as well as lower costs in patients treated with NPWT [96,98,100,103] .…”
Section: Antimicrobial Prophylaxismentioning
confidence: 99%
“…It has also been shown to positively influence time to healing in high risk wounds when compared with conventional remedies in an early phase of treatment . An enormous amount of clinical data on various cohort studies, case series, and meta‐analyses have been reported in the literature claiming various positive clinical effects of topical negative pressure therapy on open and complicated wounds . It has been reported to reduce the number of dressing changes, patient‐related pain, and the length of hospital stay and also to alter molecular mechanisms at the genetic level .…”
Section: Introductionmentioning
confidence: 99%
“…6,[18][19][20] In these reports, the sternum was debrided, re-sutured, re-wired, or left open and covered with the muscle flaps. More recently, the addition of negative pressure wound pressure therapy [21][22][23][24][25][26][27] 10 muscles as a single myocutaneous unit. There is a suggestion in the adult literature that the use of pectoralis major muscle advancement flaps alone leads to decreased shoulder strength when measured objectively.…”
Section: Discussionmentioning
confidence: 99%